2007
DOI: 10.1105/tpc.107.054833
|View full text |Cite
|
Sign up to set email alerts
|

BIN4, a Novel Component of the Plant DNA Topoisomerase VI Complex, Is Required for Endoreduplication in Arabidopsis

Abstract: How plant organs grow to reach their final size is an important but largely unanswered question. Here, we describe an Arabidopsis thaliana mutant, brassinosteroid-insensitive4 (bin4), in which the growth of various organs is dramatically reduced. Small organ size in bin4 is primarily caused by reduced cell expansion associated with defects in increasing ploidy by endoreduplication. Raising nuclear DNA content in bin4 by colchicine-induced polyploidization partially rescues the cell and organ size phenotype, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 43 publications
5
131
0
2
Order By: Relevance
“…Phvul.011G213300 is an ortholog of Arabidopsis thaliana BB, a component of the ubiquitin ligase degradation pathway that controls flower and stem size 38 , and Phvul.009G040200 is an ortholog of BIN4, which regulates cell expansion and final plant size 39 . Multiple candidate genes for domestication were also components of nitrogen metabolism pathways, which directly affect plant size.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Phvul.011G213300 is an ortholog of Arabidopsis thaliana BB, a component of the ubiquitin ligase degradation pathway that controls flower and stem size 38 , and Phvul.009G040200 is an ortholog of BIN4, which regulates cell expansion and final plant size 39 . Multiple candidate genes for domestication were also components of nitrogen metabolism pathways, which directly affect plant size.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…The transgenic lines with CDKB2;1pro:GUS or CYCB1;1-GUS were previously described by Adachi et al (Adachi et al, 2006) and Breuer et al (Breuer et al, 2007). The mp, bdl and van3 mutants were in Lansdberg erecta (Ler) ecotype and axr2-1, HS:axr3-1, pid, yuc1 yuc4 yuc10 yuc11 and ipt3 ipt5 ipt7 mutants were in Columbia (Col) ecotype.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Likewise, there are numerous experimental data reported for ploidy-dependent cell expansion (e.g. SugimotoShirasu et al, 2005;Breuer et al, 2007;De Veylder et al, 2002), whereas almost no examples have been found so far for cell expansion-induced endoreduplication.…”
Section: How Does Cell Cycle Transition Link With the Initiation Of Cmentioning
confidence: 99%
“…Many recent studies have shown that trichome cell size is often positively linked with their ploidy level (Hulskamp et al, 1994;Perazza et al, 1999;Sugimoto-Shirasu et al, 2005;Breuer et al, 2007). To test whether an increase in trichome cell size in gtl1 is accompanied by an increase in trichome ploidy, we visualized the nuclear DNA of fully mature trichomes isolated from the fourth and fifth leaves of 24-d-old plants using 49,6-diamidino-2-phenylindole (DAPI) staining.…”
Section: An Increase In Trichome Cell Size Is Accompanied By An Incrementioning
confidence: 99%